Aktivitas antioksidan produk nutrasetikal powder drink dari sari kulit bawang merah brebes (Allium cepa L. var. aggregatum): Antioxidant activity of nutraceutical powder drink products from brebes red onion peel juice (Allium cepa L. var. aggregatum) - Febriani, Alik Kandhita; Purwanti, Yunika; Balfas, Rifqi Ferry; Maesarah, Ifani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Red onion peel (Allium cepa L. var. aggregatum) is waste from red onion processing products whose utilization has not been maximized. It is known that red onion peel contains bioactive compounds such as flavonoids, anthocyanins and phenolic acids, which have antioxidant potential. Even onion peels have higher antioxidant activity than the bulb. The aim of this research is to make powder drink from Brebes red onion peels with a red onion peel concentration of 20% (SKB20), 40% (SKB40) and 60% (SKB60). Apart from that, this research also aims to evaluate the antioxidant activity of powder drink compared to onion peel juice. Red onion peel extraction uses a filtering process with water. This powder drink was made using the foam mate drying method. The antioxidant activity was measured using the DPPH method. In phytochemical testing, red onion peel contains flavonoids, saponins, terpenoids and polyphenols. The antioxidant activity test results for the red onion peel juice, powder drink with SKB20, SKB40, SKB60 formulas were 151,70 ± 0,10 ppm, 726,77 ± 0,22 ppm, 647,14 ± 0,25 ppm, 192,3 ± 0,25 ppm respectively. The highest IC50 value was SKB60 formula, which is an active antioxidant in the weak antioxidant category. At concentrations of 20% (SKB20) and 40% (SKB40), the IC50 showed non-active antioxidants. These results showed that red onion peel made into powder drink decreases antioxidant activity compared to the antioxidant activity of onion peel juice (151,7 ppm).